Clinicians’ adherence to guidelines for the preoperative management of direct oral anticoagulants in a tertiary hospital: a retrospective study - Jean Terrier; Amélie Mach; Pierre Fontana; Fanny Bonhomme; Alessandro Casini (BMC Anesthesiology, 2023)
Abstract Introduction Despite clear, relatively easy-to-use guidance, many clinicians find the preoperative management of direct oral anticoagulants (DOACs) challenging. Inappropriate management can delay procedures and lead to haemorrhagic or thromboembolic complications. We aimed to describe preoperative management practices regarding DOACs in a tertiary hospital and clinicians’ adherence to in-house recommendations. Method We included all patients being treated with DOACs who underwent elective surgery in 2019 and 2020 (n = 337). In-house recommendations for perioperative management were largely comparable to the 2022 American College of Chest Physicians guidelines. Results Typical patients were older adults with multiple comorbidities and high thrombotic risk stratification scores, and 65.6% (n = 221) had not undergone recommended preoperative anticoagulation management protocols. Patients operated on using local anaesthesia (adjusted OR = 0.30, 95%CI 0.14–0.66; p < 0.01) were less likely to have been treated following institutional recommendations, but no association between their procedure’s bleeding risk and adherence was found. Clinicians’ failures to adhere to recommendations mostly involved late or non-indicated interruptions of anticoagulation treatment (n = 89, 26.4%) or inappropriate heparin bridging (n = 54, 16.0%). Forty-five (13.3%) procedures had to be postponed. Incorrect preoperative anticoagulation management was directly responsible for 12/45 postponements (26.7% of postponements). Conclusion This study highlights clinicians’ low adherence rates to institutional recommendations for patients treated with DOACs scheduled for elective surgery in a tertiary hospital centre. To the best of our knowledge, this is the first clinical study addressing the issue of clinicians’ adherence to guidelines for the preoperative management of DOACs. Going beyond the issue of whether clinicians are knowledgeable about guidelines or have them available, this study questions how generalisable guidelines are in a tertiary hospital managing many highly polymorbid patients. Further studies should identify the causes of poor adherence.